Use of Reflective Tape to Detect Ultrasound Transducer Movement: A Validation Study - Lisa Mohr; Lutz Vogt; Jan Wilke (Life, 2021)
During dynamic ultrasound assessments, unintended transducer movement over the skin needs to be prevented as it may bias the results. The present study investigated the validity of two methods quantifying transducer motion. An ultrasound transducer was moved on a pre-specified 3 cm distance over the semitendinosus muscle of eleven adults (35.8 ± 9.8 years), stopping briefly at intervals of 0.5 cm. Transducer motion was quantified (1) measuring the 2-D displacement of the shadow produced by reflective tape (RT) attached to the skin and (2) using a marker-based, three-dimensional movement analysis system (MAS). Differences between methods were detected with Wilcoxon tests; associations were checked by means of intraclass correlation coefficients (ICC 3.1) and Bland–Altman plots. Values for RT (r = 0.57, p < 0.001) and MAS (r = 0.19, p = 0.002) were significantly higher than true distances (TD). Strong correlations were found between RT and TD (ICC: 0.98, p < 0.001), MAS and TD (ICC: 0.95, p < 0.001), and MAS and RT (ICC: 0.97, p < 0.001). Bland–Altman plots showed narrow limits of agreement for both RT (−0.49 to 0.13 cm) and MAS (−0.49 to 0.34 cm) versus TD. RT and MAS are valid methods to quantify US transducer movement. In view of its low costs and complexity, RT can particularly be recommended for application in research and clinical practice.